La Madonna della Clemenza, l’incidence de la réintégration picturale sur le maintien des fonctions portées par l’œuvre restaurée - Stéphanie Ricordeau (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
In the Basilica Santa Maria in Trastevere in Rome is kept the Madonna della Clemenza, an encaustic on canvas and wood, from  the sixth or seventh century. This painting, still an object of worship and devotion, has emerged as a major work of the Christian Occident, both by its beautiful realization and  by the historical testimony that it represents. The restoration, done at the Istituto Centrale di Restauro directed at the time by Cesare Brandi, confronted the restorers to intervention options that appear as fundamental methodological problems.Among the many questions which emerged, the choice of pictorial reintegration of this highly lacunar work occupies a special place. Starting from the basic premise that we cannot think of the restoration of works of art, particularly of religious works, without taking into account their functions and their use value, it is necessary to question how the religious function is affected or not by the choice of pictorial reintegration.This imperative requires the identification of significant elements of the work of art, what make sense for the believer, since it’s their readability that will maintain the religious function. This appears to us as a prerequisite methodology to guide the development of the protocol of restoration.